Respuesta :
y=4x-7......(1)
y=x-3.........(2)
(2)×4
4y=4x-12......(3)
(1)-(3)
y=-5/3
x=4/3
Answer:
one solution
Step-by-step explanation:
Given the 2 equations
y = 4x - 7 → (1)
y = x - 3 → (2)
Substitute y = 4x - 7 into (2)
4x - 7 = x - 3 ( subtract x from both sides )
3x - 7 = - 3 ( add 7 to both sides )
3x = 4 ( divide both sides by 3 )
x = [tex]\frac{4}{3}[/tex]
Substitute this value into (2) for corresponding value of y
y = [tex]\frac{4}{3}[/tex] - 3 = [tex]\frac{4}{3}[/tex] - [tex]\frac{9}{3}[/tex] = - [tex]\frac{5}{3}[/tex]
Solution is ( [tex]\frac{4}{3}[/tex], - [tex]\frac{5}{3}[/tex])